Sound and thermal insulation properties of flax/low melt PET needle punched nonwovens. Issue 2 (17th February 2019) - Muthukumar, N.; Thilagavathi, G.; Neelakrishnan, S.; Poovaragan, P.T.
ABSTRACT: Noise pollution is an ever increasing problem in the world because of the industrial revolution. Recently, researchers have begun investigating natural fiber composites as potential materials for the manufacture of sound absorption structures. In this work, flax/low melting point polyester needle punched nonwoven fabrics were manufactured and characterized for sound and thermal insulation applications. Nonwovens were developed by blending flax fibers with low melt PET at three blend ratios (10%, 20%, and 30%) with 7 mm and 10 mm needle penetration depth. The test results showed that there was a decrease in thermal resistance value with increase in low melt PET % and needle penetration depth. The developed nonwovens had better sound insulation value at medium and high frequency. There was no significant change in sound insulation value with increase in low melt PET %.